Voices of change: experiences of early women urology residents — a single institution qualitative research study - Aurora J. Grutman (BMC Medical Education)
Abstract Objective To understand the experiences of early women urology residents at a single institution, as told in their own words. Methods A convenience sample of women residents who trained at the Brady Urological Institute between 1980 and 2022 was chosen. During the investigated period, 15 women trained at the Brady; all 15 were invited to participate. Participants were provided written consent and assured of anonymity. In semi-structured interviews guided by a set of IRB-approved questions, participants discussed personal backgrounds, medical school experiences, and residency experiences. Participants provided advice to future women in urology. Interviews were recorded with Audacity 3.0.5 or Zoom, and audio files were transcribed using NVivo 14.23.0. Results A total of 10 interviews were conducted between July 2023 and February 2024. Childhood role models influenced many participants’ initial interest in medicine, although most discovered urology during medical school. Participants valued the quality of training, mentorship opportunities, proximity to family, and program ethos when selecting a residency program. During residency, participants faced gender-specific challenges due to patient resistance and difficulties balancing professional and personal commitments. Despite these challenges, participants expressed optimism about the future of women in urology. Conclusions This study provides insights into the professional development of women urology residents. The participants were part of an early cohort of women in urology and expressed excitement for the future of the field. While the study reflects the experiences of women at just one institution, it provides a foundation for more comprehensive research on women’s experiences in urology and in medicine more broadly. Clinical trial number Not applicable.